Poverty Map of the Palestinian Territories : Palestinian Expenditure and Consumption Survey 2016 and Census 2017 - Atamanov, Aziz; Palaniswamy, Nethra (World Bank, Washington, DC, 2020)
This technical report describes the methodology and data used to produce small area poverty estimates for the Palestinian territories. The first section presents the methodology. The second section describes the data, and the technical challenges in estimating poverty at the locality level. The third section discusses selection of the best model, its performance and conducts validation exercises. The fourth section shows poverty and inequality estimates for different levels.